PENGARUH METODE LATIHAN GAYA SELF CHECK, KONVERGEN DAN KEDISIPLINAN TERHADAP KETERAMPILAN DASAR BERMAIN SEPAKBOLA DI SSB BINA MUDA MUNGKA - Rahmad, Hari Adi (Jurnal Curricula, 2019)
Based on the observations of researchers in the field shows that skill of the player SSB Bina Muda District of Mungka are still low, there are many players who have not yet mastered the basic techniques of football. This research aim to reveal the effect of self-check style training method, convergent discovery style and discipline to skill play of football. This type of research is Quasy Experiment. The research population was entire player of age 12 years of SSB Bina Muda which amount to 82 people.While  sample in this research was 44 people after conducted the division of  group 27% with high discipline and 27% with low discipline. The instrument used in this research is a test of skill to play football. Data were analyzed by using variant analysis two-lane (ANAVA 2x2). The results of data analysis showed that (1) there are  differences between the groups playing football skills by training methods self check with group training methods invention of convergent style. (2) there are  differences between the groups playing football high level of discipline and lower level of discipline (3) there are interaction between practice style with discipline to force an increase in the basic skills of playing football (4) at a high level of discipline self check style training method is better than exercise style discovery method converges to an increase in the basic skills of playing football (5) while in the lower level of discipline discovery style training method converges better than self check style training methods to the improvement of the basic skills of playing football.